Prediction of Secondary Metabolite Compounds in Lotus (Nelumbo nucifera Gaertn.) Targeting Androgen-α Receptors for Breast Cancer Treatment Using Molecular Docking - Siagian, Virginia Heaven Mariboto; Destia, Melsa; Andini, Nasywa Putri; Yustiandini, Benedicta Andrea; Adhinagoro, Bagus; Salsabila, Shela; Muchtaridi, Muchtaridi (Indonesian Society for Cancer Chemoprevention, 2024)
Breast cancer (BC) is a malignant tumor that grows in the breast tissue and can spread to other organs. BC is often found at an advanced stage and therefore has a poor prognosis. With 68,858 cases, BC is the most common type of cancer in Indonesia. The development of breast carcinoma is strongly influenced by steroid hormones and their receptors, such as estrogen, progesterone, and androgen. Androgen receptors (AR) are found more (70-90%) compared to estrogen receptors (60-80%) and progesterone receptors (50-70%). Therefore, research on natural compounds that inhibit cancer cell proliferation influenced by AR needs to be increased. The lotus plant (Nelumbo nucifera Gaertn.) has been used as a traditional herbal medicine and food in Asia. Bioactive compounds in lotus have therapeutic potential against BC. In the pharmacophore screening results, five hit compounds were found: isorhamnetin, luteolin, catechin, kaempferol, and apigenin. The compound with the best pharmacophore fit score value is isorhamnetin with a value of 41.31, while the compound with the best binding affinity to AR is kaempferol with a binding affinity of -9.44 and an inhibitor constant of 121.12 nM.Keywords: breast-cancer, androgen-α receptor, lotus, molecular docking.